Economic Implications of Coronary Arterial Revascularization from Bangladesh Perspective (Cardiovascular Journal, 2020)
Background: There has been a radical improvement lately both for coronary artery bypass graft (CABG) and percutaneous coronary intervention (PCI) in Bangladesh. Besides the clinical goals, the economic impact of these procedures is very important as well. Out of pocket spending is the major payment strategy for healthcare in Bangladesh. It is estimated that the poverty headcount increased by 3.5% due to out of pocket healthcare payments.Methods: Data on patients’ expenditure for CABG and PCI in seven Bangladeshi hospitals were collected between 16th and 30th August, 2020. Several models were created, where the cost of CABG was compared with that of PCI in each of these hospital settings.Results: In the two public hospitals CABG is much cheaper than PCI. However, in mid-level expensive hospitals the cost of PCI with 2 stents is comparable with that of CABG, but with 3 or more stents, PCI becomes more expensive. In the big corporate hospitals, CABG tends to be relatively more expensive. The basic treatment expenditure of a patient suffering from triple vessel ischemic heart diseases may range from Taka 50000 to Taka 415000.Conclusion: In Bangladesh CABG is much cheaper than multi-stent PCI in the public and medium range private hospitals. CABG in corporate hospitals may be equal or even more expensive than PCI. IHD may contribute to national poverty as it may turn into a catastrophic health event for the patient’s family.Cardiovasc. j. 2020; 13(1): 56-61